Genetic hypervariability of telomere-related sequences is associated with meiosis in Plasmodium falciparum. - Vernick, K D (1988)
Sequences related to those near chromosome telomeres in the human malaria parasite, Plasmodium falciparum, were extremely unstable during a genetic cross between two different clonal genotypes. Many progeny of the heterologous cross displayed telomere-homologous restriction fragments found in neither parent. A significant number of the new fragments resulted from rearrangements at chromosome-internal locations which were bounded by more complex tracts of DNA sequence. The same instability was not seen to arise during an inbreeding cross, nor during mitotic replication of parasites. Thus, a form of genetic hypervariability results from molecular events which occur during meiotic reduction and is apparent only in a cross between heterologous strains of parasite. Since other sequences were entirely stable under the same conditions, it appears that chromosome-internal blocks of telomeric sequences in the P. falciparum genome may designate conditionally unstable chromosomal domains. We discuss some potential implications of these findings for the population biology of P. falciparum.